Nile Red Incubation Time Before Reading Fluorescence Greatly Influences the Yeast Neutral Lipids Quantification - Ramírez-Castrillón, Mauricio; Jaramillo-Garcia, Victoria P.; Lopes Barros, Helio; Pegas Henriques, João A.; Stefani, Valter; Valente, Patricia (Frontiers in Microbiology, 2021)
High-throughput screening methodologies to estimate lipid content in oleaginous yeasts use Nile red fluorescence in a given solvent and optimized excitation/emission wavelengths. However, Nile red fluorescence stabilization has been poorly analyzed, and high variability occurs when relative fluorescence is measured immediately or a few minutes after dye addition. The aim of this work was to analyze the fluorescence of Nile red at different incubation times using a variety of solvents and oleaginous/non-oleaginous yeast strains. We showed that fluorescence stabilization occurs between 20 and 30 min, depending on the strain and solvent. Therefore, we suggest that fluorescence measurements should be followed until stabilization, where Relative Fluorescence Units should be considered after stabilization for lipid content estimation.